Design and analysis of multiple charge controller systems in hybrid power generation. Issue 4 (March 2021) - Hidayat, M N; Wulandari, A D; Ronilaya, F
Abstract: Currently, the demand for electricity is increasing from time to time. While the existence of fossil fuels to generate electricity is depleted. This condition resulted in the use of renewable energy source in electrical power generation. Since the electricity generated from renewable energy sources is not constant because it is depending on the climatic conditions, a controller of the charging and discharging mechanism on a battery is necessary for it to work optimally for storing electricity. To overcome this problem, one of the solutions is by applying hybrid power generation technology. One the important equipment related to this technology is the application of a charge controller. The charge controller here is used to control the charging and discharging mechanism to store electricity in a battery. The charge controller is found mainly in a standalone mechanism where the controller only has one input from one renewable energy source. If we have more than one renewable sources, therefore we need a charge controller with multiple input terminals. This study examines and compares the design of a standalone charge controller and a multiple input charge controller. The result shows that it is more efficient to use a multiple input charge controller rather than to use two single input charge controller.